Contrast‐enhanced ultrasound after successful cryoablation of benign and malignant renal tumours: how long does tumour enhancement persist?. Issue 3 (6th February 2021) - Bertolotto, Michele; Campo, Irene; Sachs, Camilla; Ciabattoni, Riccardo; Cicero, Calogero; Drudi, Francesco Maria; Derchi, Lorenzo E; Cova, Maria Assunta
Abstract: Introduction: To investigate how long successfully ablated tumours take to become completely avascular at CEUS after cryoablation. Methods: Ninety‐five patients had percutaneous cryoablation of 103 renal tumours investigated at CEUS on post‐operative day one. If the lesion was avascular, a contrast‐CT/MR was scheduled six months after the procedure, while CEUS was repeated if the lesion still displayed enhancement, until the disappearance of intralesional vascularity. Technical success was defined when the tumour was covered completely by the ablation zone. Technique efficacy was assessed at six months of follow‐up. Results: Technical efficacy was obtained for 101/103 cryoablations, 56% of which (57/101) were avascular on post‐operative day one. After one week, two weeks, one month 83%, 91% and 100% of these 101 lesions, respectively, were avascular. Two tumours were unsuccessfully treated. They displayed persistent intralesional vascularity at CEUS one month after the procedure. Conclusions: After cryoablation, obtaining CEUS before one month may be misleading. When technical efficacy is obtained, disappearance of intralesional enhancement is observed within two weeks in the majority of cases (91%), but can persist until one month. Identification of tumour enhancement after one month may be concerning for residual viable tumour.